2019
DOI: 10.1080/10408444.2019.1573804
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response for assessing the cancer risk of inorganic arsenic in drinking water: the scientific basis for use of a threshold approach

Abstract: The biologic effects of inorganic arsenic predominantly involve reaction of the trivalent forms with sulfhydryl groups in critical proteins in target cells, potentially leading to various toxicologic events including cancer. This mode of action is a threshold process, requiring sufficient concentrations of trivalent arsenic to disrupt normal cellular function. Nevertheless, cancer risk assessments for inorganic arsenic have traditionally utilized various dose-response models that extrapolate risks from high do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 309 publications
(514 reference statements)
0
34
0
3
Order By: Relevance
“…29 Our analysis was restricted to a linear, non-threshold model, and did not address other dose-response relations. While non-linear models have been proposed to explain the association between arsenic exposure and prevalence of skin lesions, 5 we selected the linear model because it represents a more conservative approach, and it is adopted by regulatory authorities such as EPA for carcinogenic effects. 30 Furthermore, we based on analysis on average (lifetime) exposure, despite the fact that other aspects of exposure such as duration peaks are additional important components of arsenic toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Our analysis was restricted to a linear, non-threshold model, and did not address other dose-response relations. While non-linear models have been proposed to explain the association between arsenic exposure and prevalence of skin lesions, 5 we selected the linear model because it represents a more conservative approach, and it is adopted by regulatory authorities such as EPA for carcinogenic effects. 30 Furthermore, we based on analysis on average (lifetime) exposure, despite the fact that other aspects of exposure such as duration peaks are additional important components of arsenic toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…3 Exposure to high levels of arsenic in drinking water has been associated with increased occurrence of skin lesions, including alteration of pigmentation and keratosis (Chen et al, 1997). [4][5][6] Hyperpigmentation (melanosis) consists of diffuse dark-brown or blackish areas on the skin of the neck, trunk, or extremities, as well as oral mucosa, and diffuse or spotted pigmentation on the trunk and other parts of the skin. Hypopigmentation (leukomelanosis) is characterized by whitish patches, also referred to as raindrop pigmentation.…”
Section: Introductionmentioning
confidence: 99%
“…As exposure is also associated with a low expression of peroxisome proliferator-activated receptor gamma resulting in a decrease of sensitization of insulin, one of the mechanisms accounting for induction of diabetes mellitus [ 44 , 45 ]. The carcinogenic effect of As has been recognized [ 46 , 47 ]. An in vitro study revealed that even low doses of As induced DNA damage (strand breakage and oxidative stress) [ 48 ].…”
Section: Air Pollution: the Role Played By Particulate Matter And mentioning
confidence: 99%
“…Trivalent arsenic tends to show cytotoxicity at tissue concentrations in the µM range (> 0.1-10.0 µM (7.5-750 µg/L) [29], while pentavalent methylated arsenic is only toxic in the mM range (i.e., at >75 mg/L or >75,000 µg/L) [30]. Thus, a cellular concentration of >0.1 ug/L (7.5 ug/L) has been considered to be a reasonable estimate for the minimum cellular concentration required for obtaining a biological effect, which may be either adaptive or toxic [31]. Effects of arsenic at low concentrations on the order of 0.1 uM (7.5 ug/L) appear to be adaptive, while concentrations above 1 uM (75 ug/L) are clearly cytotoxic [32].…”
Section: Arsenic Toxicologymentioning
confidence: 99%
“…Effects of arsenic at low concentrations on the order of 0.1 uM (7.5 ug/L) appear to be adaptive, while concentrations above 1 uM (75 ug/L) are clearly cytotoxic [32]. Urinary levels of >0.1 uM (>7.5 ug/L) trivalent arsenic in humans are estimated to be associated with drinking water arsenic levels of 50-100 ug/L [31]. The threshold for potentially adverse cellular effects from exposure to inorganic arsenic in drinking water is thought likely to occur at urinary concentrations of trivalent arsenic above 0.2 um (15 ug/L), which corresponds to drinking water total arsenic concentrations above 65 ug/L [33].…”
Section: Arsenic Toxicologymentioning
confidence: 99%